2010
DOI: 10.1007/s12274-010-1037-x
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and application of Ag-chemically converted graphene nanocomposite

Abstract: An in situ chemical synthesis approach has been employed to prepare an Ag-chemically converted graphene (CCG) nanocomposite. The reduction of graphene oxide sheets was accompanied by generation of Ag nanoparticles. The structure and composition of the nanocomposites were confirmed by means of transmission electron microscopy (TEM), atomic force microscopy (AFM) and X-ray diffraction. TEM and AFM results suggest a homogeneous distribution of Ag nanoparticles (5-10 nm in size) on CCG sheets. The intensities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
240
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(259 citation statements)
references
References 71 publications
16
240
0
Order By: Relevance
“…NaBH 4 was used to reduce Ag ions to generate GO nanosheet-based nanocomposites. 73 Al-Marri et al 74 reported the simultaneous reduction of both GO and Ag ions using Pulicaria glutinosa plant extract as the reducing agent. GO-Ag nanocomposites have been prepared with AgNO 3 using various reducing agents such as sodium citrate, 69 ammonia, 52 and poly(N-vinyl-2-pyrrolidone).…”
Section: Results and Discussion Synthesis And Characterization Of Rgomentioning
confidence: 99%
“…NaBH 4 was used to reduce Ag ions to generate GO nanosheet-based nanocomposites. 73 Al-Marri et al 74 reported the simultaneous reduction of both GO and Ag ions using Pulicaria glutinosa plant extract as the reducing agent. GO-Ag nanocomposites have been prepared with AgNO 3 using various reducing agents such as sodium citrate, 69 ammonia, 52 and poly(N-vinyl-2-pyrrolidone).…”
Section: Results and Discussion Synthesis And Characterization Of Rgomentioning
confidence: 99%
“…In the last years, the ability of combining well with metallic nanoparticles producing nanocomposites with promising applications such as chemical sensors, energy and hydrogen storage systems and catalysts, among others, has captured the interest of a number of researchers; the advantage, beyond the already mentioned characteristics of graphene, is that we can add specific properties associated to the inorganic nanoparticles like magnetic, optical, electrical, catalytic and others (Hassan, Abdelsayed et al 2009;Kamat 2009). The majority of the publications related to the preparation and applications of this new class of graphene based nanocomposites uses noble metals like gold (Goncalves, Marques et al 2009;Hong, Bai et al 2010), platinum (Si and Samulski 2008), palladium (Scheuermann, Rumi et al 2009) and silver (Shen, Shi et al 2010); however, there is also a growing interest in the use of other metals like, iron, cooper, tin and cobalt. Some of the published papers about the preparation of graphene/metal nanocomposites makes use of organic spacers, like octadecylamine, to anchor the metallic nanoparticles to the graphene surface or organic solvents such as tetrahydrofuran, methanol, and ethylene glycol (Muszynski, Seger et al 2008).…”
Section: Inorganic Functionalization Of Graphene Sheetsmentioning
confidence: 99%
“…26 Graphene-based nanomaterials have been shown as excellent and suitable platforms for anchoring silver nanoparticles (AgNPs) for the production of graphene-Ag nanocomposites used as antimicrobial and anticancer agents. [27][28][29][30][31][32][33][34][35] Among several metallic nanoparticles, AgNPs are widely used in industry as well as biomedical applications due to their unique physical, chemical, and biological properties, particularly antibacterial, antiviral, antifungal, anti-inflammatory, anticancer, and antiangiogenic activities. Although AgNPs are presented as very attractive molecules in various therapeutic and industrial applications, they have a strong tendency to aggregate in aqueous solutions and are susceptible to aggregate into large particles owing to their high surface energy, resulting in deterioration of their unique chemical properties and loss of their antibacterial activities, which leads to a decrease in various biological activities.…”
Section: Introductionmentioning
confidence: 99%